A synaptic temperature sensor for body cooling - Kamm, Gretel B.; Boffi, Juan C.; Žuža, Kristina; Nencini, Sara; Campos, Joaquín; Schrenk-Siemens, Katrin; Sonntag, Ivo; Kabaoğlu, Burçe; Abd El Hay, Muad; Schwarz, Yvonne; Tappe-Theodor, Anke; Bruns, Dieter; et al. (Neuron, 2021)
Deep brain temperature detection by hypothalamic warm-sensitive neurons (WSNs) has been proposed to provide feedback information relevant for thermoregulation. WSNs increase their action potential firing rates upon warming, a property that has been presumed to rely on the composition of thermosensitive ion channels within WSNs. Here, we describe a synaptic mechanism that regulates temperature sensitivity of preoptic WSNs and body temperature. Experimentally induced warming of the mouse hypothalamic preoptic area in vivo triggers body cooling. TRPM2 ion channels facilitate this homeostatic response and, at the cellular level, enhance temperature responses of WSNs, thereby linking WSN function with thermoregulation for the first time. Rather than acting within WSNs, we - unexpectedly -find TRPM2 to temperature-dependently increase synaptic drive onto WSNs by disinhibition. Our data emphasize a network-based interoceptive paradigm that likely plays a key role in encoding body temperature and that may facilitate integration of diverse inputs into thermoregulatory pathways.